Anti-tumor effects of a novel retinoic acid metabolism blocking agent VN/14-1 in the N-methyl-N-nitrosourea-induced rat mammary carcinoma model and its effects on the uterus - Goss, Paul E. (2011)
VN/14-1 [4-(±)-(1H-Imidazol-1-yl)-(E)-retinoic acid], a novel retinoic acid metabolism blocking agent (RAMBA), works by inhibiting the breakdown of all-trans-retinoic acid. The purpose of this study was to evaluate the anti-tumor effects of VN/14-1 on the N-methyl-N-nitrosourea (MNU)-induced rat mammary carcinoma model, and peripheral organ effects on the uteri of immature ovariectomized (OVX) rats. In tumor burden experiments, after 56 days of administration of VN/14-1 5, 10, and 20 mg/kg/day, significant tumor reductions in mean tumor weight of 19.1, 34.4, and 44.3%, compared to tumors in control animals occurred. Cumulative tumor growth was also significantly slower in a dose-dependent manner in groups receiving 5, 10, and 20 mg/kg/day of VN/14-1 compared to growth rates in the control group. Tumor apoptosis was significant increases in animals treated with 5, 10, and 20 mg/kg/day of VN/14-1. In uterotrophic experiments, immature OVX rats given VN/14-1 significantly reduced uterine weight and blocked endometrial stimulation induced by unopposed β-estradiol (E2). In both rat models, adverse toxicities included weakness, anorexia, and reduction in body weight in the groups given the highest dose of 20 mg/kg/day. In summary, VN/14-1 inhibited tumor growth in the MNU-induced estrogen receptor (ER)-positive rat mammary tumor model, and antagonized the stimulatory effect of estrogens on the uterus. The studies suggest that VN/14-1 may be a useful novel therapy for ER-positive breast cancer.